Designing and implementing a test for measuring cultural dimensions in primary school. (September 2018) - Gelerstein, Damián; Nussbaum, Miguel; López, Ximena; Cortés, Ana; Castillo, Cristóbal; Chiuminatto, Pablo; Ovalle, Francisca
Abstract: Cognition and culture are deeply intertwined as there are important cross-cultural differences in the cognitive development of individuals. Although there are a large number of studies on the subject of culture, these are qualitative in nature and not focused on school contexts. Our aim is to develop a quantitative instrument for primary education that determines the cultural texture within an individual institution, as well as among different kinds of schools. For this purpose, Hofstede's original instrument was adapted, taking into consideration the characteristics and practices of primary school students. A factor analysis and complementary qualitative analysis of the factors obtained from 783 surveys (administered to third and fourth graders) led to the creation of five dimensions, which contrasted with Hofstede's theoretical dimensions. These dimensions include Value of School Achievement, Value of Institutional Structure, Resistance to change, Normative versus Affective and Value of Equality in the Production of Knowledge. Furthermore, this new set of dimensions was a more accurate representation of the school context and the values held by primary school students. Significant differences were found in three of the dimensions when analyzing the cultural differences of the sample and taking into account the students' socioeconomic background. These findings are important as they reveal the presence of subcultures within a given society, which are determined by belonging to a certain socioeconomic class. Measuring cultural values among primary school students contributes to the creation of educational models, the design of educational institutions and the development of public policy since new structures cannot succeed without adequate cultural support.